Expectations of Health Researchers From Academic Social Network Sites: Qualitative Study - Mohammad Dehghani; Mehdi Kahouei; Shahin Akhondzadeh; Bita Mesgarpour; Reza Ferdousi (JMIR Publications, 2021)
BackgroundToday, academic social network sites' role in improving the quality of education and how investigators conduct their research has become more critical. ObjectiveThis study aimed to investigate Iranian health researchers' requirements for academic social network sites from a low-income country perspective. MethodsThis qualitative study with a phenomenological approach was done in 2020. In this study, 23 researchers in the health system were selected by purposive sampling. Semistructured interviews were used to collect data. Data were analyzed by MaxQDA-10 software and the content analysis method. ResultsWe identified 2 categories of functional and technical characteristics in the study participants' expectations. Functional characteristics included facilitating communication and team activities, managing scientific publications, enhancing the process of conducting research, being informative, and sharing and trading laboratory materials and equipment. Technical characteristics of an academic social network include user management capabilities, high security and privacy, being user-friendly, and other technical features. ConclusionsHealth researchers emphasized 2 functional and technical characteristics required to meet academic social network sites' expectations.